Strategi Pemasaran Pembiayaan Arrum Haji Dalam Meningkatakan Jumlah Nasabah di Unit Pegadaian Syariah (UPS) Cirebon Bisnis Center - Fajrin, Oktavia; Muamar, Afif (TAWAZUN: Journal of Sharia Economic Law, 2019)
Hajj Financing for Micro Business (Arrum) Hajj in Pegadaian Syariah is relatively new, because this product was only launched in 2016. For this new product an introduction is needed to be able to attract the interest of the community. Therefore, this study aims to determine marketing strategies, the mechanism of Arrum Hajj financing registration, and to determine customer responses to Arrum Hajj products at the Pegadaian Syariah Cirebon Business Center. This study used a qualitative method with a descriptive analytical approach, and this research resulted in a marketing strategy conducted by the CBC Sharia Pawnshop Unit using a 4p strategy, namely Product, Price, Place, and Promotion. The results of this study found that the price and place strategy had been determined by the head office and the Pegaadian Sharia branch office. While the product strategy has been going very well, by providing services and comfort, as well as promotion strategies carried out by sharia pawnshops are quite diverse such as holding seminars, socialization, cross selling techniques and so on. Hajj arrum registration mechanism is in accordance with existing procedures. And the response given by Arrum Hajj financing customers is very good, because with the availability of Arrum Hajj products can ease the burden on customers and can quickly get a portion of Hajj.